Multiply-charged ion nanobeams. (16th June 2008) - Cassimi, A.; Muranaka, T.; Maunoury, L.; Lebius, H.; Manil, B.; Huber, B.A.; Ikeda, T.; Kanai, Y.; Kojima, T.M.; Iwai, Y.; Kambara, T.; Yamazaki, Y.; et al.
Due to the strong evolution in the field of nanotechnologies and the continuous miniaturisation of electronic components, multiply-charged ion nanobeams would be a promising tool in this field of research. Either for surface modification or local (nanometre scale) surface analysis purposes, studying the feasibility of such beams is of strong interest. In the present contribution, we present a focusing technique based on the self-organised charge-up of a simple glass 'funnel'.